Impact of measurement location on direct mitral regurgitation quantification using four-dimensional flow cardiovascular magnetic resonance - Adarsh Aratikatla; Taimur Safder; Gloria Ayuba; Vinesh Appadurai; Aakash Gupta; Michael Markl; James Thomas; Jeesoo Lee (Journal of Cardiovascular Magnetic Resonance)
Background: Four-dimensional (4D) flow cardiovascular magnetic resonance (CMR) shows promise for quantifying mitral regurgitation (MR) by allowing for direct regurgitant volume (RVol) measurement using a plane precisely placed at the MR jet. However, the ideal location of a measurement plane remains unclear. This study aims to systematically examine how varying measurement locations affect RVol quantification and determine the optimal location using the momentum conservation principle of a free jet. Methods: Patients diagnosed with MR by transthoracic echocardiography (TTE) and scheduled for CMR were prospectively recruited. Regurgitant jet flow volume (RVoljet) and regurgitant jet flow momentum (RMomjet) were quantified using 4D flow CMR at seven locations along the jet axis, x. The reference plane (mid-plane, x = 0 mm) was positioned at the peak velocity of the jet at each cardiac phase, and three additional planes were positioned on either side of the jet, each 2.5 mm apart. RVoljet was compared to RVolTTE, measured by the proximal isovelocity surface area method, and RVolindirect, measured by subtracting aortic forward flow volume from the left ventricle stroke volume derived from two-dimensional phase contrast at the aortic valve and a stack of short-axis cine CMR techniques. Results: RVoljet and RMomjet were quantified in 45 patients (age 63±13, male 26). In patients with RVoljet at x = 0 mm ≥ 10 mL (n = 25), RVoljet consistently increased as the plane moved downstream. RVoljet measured furthest upstream (x = −7.5 mm) was significantly lower (39±11%, p<0.001) and RVoljet measured furthest downstream (x = 7.5 mm) was significantly higher (16±19%, p<0.001) than RVoljet at x = 0 mm. RMomjet similarly increased from x = −7.5 to 0 mm (57±12%, p<0.001) but stabilized from x = 0–7.5 mm (−2±17%). From x = −7.5 to 7.5 mm, RVoljet was in consistent moderate agreement with RVolindirect (n = 41, bias = −2±24 to 8±32 mL, intraclass correlation coefficient = 0.55–0.63, p<0.001). Conclusion: The location of a measurement plane significantly influences RVol quantification using the direct 4D flow CMR approach. Based on the converging profile of RMomjet, we propose the peak velocity of the jet as the optimal position.